Zero Divisor Graph of a Lattice and Its Unique Ideal. (1st December 2019) - Deore, Rajendra; Tayade, Pramod
Abstract : Let L be a lattice with the least element 0. Let A L be the finite set of atoms with A L > 1 and Γ L be the zero divisor graph of a lattice L . In this paper, we introduce the smallest finite, distributive, and uniquely complemented ideal B of a lattice L having the same number of atoms as that of L and study the properties of Γ L and Γ B .